(untitled) (Proceedings of the International Conference on Public Health, 2017)
The selected foundling home is an established institution for the unprivileged and abandoned children. Medical and Laboratory Examinations were conducted among the fifty-two (52) children of the said institution. Respiratory Tract and skin infections are among the diseases that were noted among the subjects. While Urinary Tract Infection (UTI) is not prevalent, intestinal parasitism is common among the children in the Foundling Home. Development of an effective health monitoring program is imperative to improve the present health status of the children